Four new species and new records of the Neotropical genus Alloraphes Franz (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2020)
Four new species of Alloraphes Franz are described: A. opticus sp. n. (French Guiana), A. cayennensis sp. n. (French Guiana), A. iyonolanus sp. n. (Saint Lucia), and A. ecuadoranus sp. n. (Ecuador). They all represent the first records of Alloraphes in the listed countries. New records are given for A. jamaicae Franz, and A. yucatani Franz; the latter species, previously known to occur in Mexico (Campeche), is for the first time reported to occur also in Guatemala.